(untitled) (American Journal of Pedagogical and Educational Research, 2024)
Preparing students for professional activities, as one of the critical directions of the educational process, aims to develop professional knowledge, skills, and competencies in students. To effectively implement this process, it is necessary to design didactic opportunities, which include teaching methods and tools, as well as methods for organizing the educational process. Through didactic opportunities, it is possible to enhance professional training, develop students’ practical skills, and improve the competencies required for successful future professional activities.